Risk Factor Analysis for Placenta Retention in Maternal Delivery at the Tenriawaru Regional Hospital in Bone Regency - Andi Misnawati; Rosdiana (Indian Journal of Forensic Medicine & Toxicology, 2021)
Placenta retention issues have complications that can endanger mothers after delivery because of theirstrong association with bleeding. This research aims to determine the risk factors for placental retention inmaternal. This research was an observational analytic study with a case-control design with a sample size of68 mothers. The research was conducted at the Tenriawaru Hospital in 2020. Data collection was carried outby interview using a questionnaire. Then it was analyzed using the chi-square test. The results of the researchfor the Age variable (p-value = 0.027) show that there is a relationship between age and the incidence ofplacental retention, with the OR value: 3.4 (CL: 1.26–9.41) and for the parity variable (p-value = 0.44) therewas no relationship between parity and the incidence of placental retention, with the OR value: 0.47 (CL:0.12–1.82). It can be concluded that of the two factors the incidence of placental retention including age andparity, only age is associated with the incidence of retained placenta.